Pengelolaan Brand Awereness Aplikasi Ezurance PT Jasaraharja Putera Semarang Melalui Strategi Public Relation - Suryatiana, Putri Karima; Mardiana, Lisa (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This Public relations strategy plays a strategic role in building corporate image and increasing brand awareness, especially in the context of digital services such as the Ezurance application owned by PT Jasaraharja Putera Semarang Branch. This study aims to analyze the implementation of communication strategies carried out by the company in promoting Ezurance to the public. The approach used is PDCA (Plan, Do, Check, Action), which is applied in stages starting from the planning, implementation, evaluation, to corrective action. The strategies implemented include digital promotion through social media, participation in local events, dissemination of information through booths, and use of print media. In addition, the utilization of brand ambassadors that match the company's image is an innovative step to expand audience reach and increase campaign appeal. The results of the study indicate that the PR strategies implemented by the company have gradually succeeded in increasing brand awareness, although challenges remain due to the low level of digital literacy among the public in understanding insurance. Therefore, continuous public education and periodic evaluation are needed to ensure that the PR strategy implemented remains relevant to the development of digital trends and the changing needs of the audience